2021
DOI: 10.2147/ndt.s304567
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on the Assessment and Management of Gait Disorders in Parkinson’s Disease

Abstract: Gait dysfunction is a key defining feature of Parkinson’s disease (PD), and is associated with symptoms of freezing and an increased risk of falls. In this narrative review, we cover the putative mechanisms of gait dysfunction in PD, the assessment of gait abnormalities, and the management of symptoms caused by the inherent difficulty in walking. Our understanding of the causes of gait problems in PD has progressed in recent times, moving from neurocognitive theory to correlates of affected neuronal pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 203 publications
(250 reference statements)
0
5
1
Order By: Relevance
“…In addition, the aforementioned rheumatological deformity of the fingers and hands favours said difficulty in using devices for cutting nails, as well as the tremor present in the extremities. 9,[26][27][28][29] Regarding the results obtained in our study in the pain dimension, the patients with Parkinson's reported having discomfort and moderate pain to a greater extent than the healthy participants, although this result did not show statistically significant differences between the two groups. Previous studies highlight the issue of suffering from pain in Parkinson's patients.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In addition, the aforementioned rheumatological deformity of the fingers and hands favours said difficulty in using devices for cutting nails, as well as the tremor present in the extremities. 9,[26][27][28][29] Regarding the results obtained in our study in the pain dimension, the patients with Parkinson's reported having discomfort and moderate pain to a greater extent than the healthy participants, although this result did not show statistically significant differences between the two groups. Previous studies highlight the issue of suffering from pain in Parkinson's patients.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, the aforementioned rheumatological deformity of the fingers and hands favours said difficulty in using devices for cutting nails, as well as the tremor present in the extremities. 9 , 26 , 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…When we changed the definition of dementia to having been prescribed an anti-dementia drug (ATC class N06D), we observed an increase in the number of dementia cases, as well as higher HRs. One possible explanation for the increased number of presumed dementia cases is that anti-dementia drugs (cholinesterase inhibitors) such as rivastigmine have been trialled with trending positive effects on gait stability and fall frequency in PwP, and may therefore have been prescribed off-label for those purposes 31 . Another indication for starting treatment with rivastigmine among PwP might be hallucinations, as reviewed by Samudra et al 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Gait is a basic characteristic of human life deeply tied to the quality of life [1]. While it is usually taken for granted, gait as an activity is complex and rich in information.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is also the most daunting. Gait disturbances exhibited in Parkinson's disease are multifaceted, with their manifestations being hard to identify, as they change and increase in complexity, depending on the disease's stage [1,3].…”
Section: Introductionmentioning
confidence: 99%